2022
DOI: 10.1017/s0007114522002070
|View full text |Cite
|
Sign up to set email alerts
|

Study on influential factors and reference values for thyroid volume in Chinese children aged 6–12 years

Abstract: The purpose of this study was to research the factors influencing thyroid volume (TVOL) in 6∼12-year-old children and update the reference values. A cross-sectional study was carried out in iodine-sufficient areas of four provinces in China. Urine, edible salt, and drinking water samples were collected from children. Children’s height, weight, and TVOL were measured. Ridge regression was used to screen variables for solving the multicollinearity problem. Quantile regression was used to analyze the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Thyroid volume is closely related to anthropometric indexes, and the effect of BSA on thyroid volume has been widely confirmed [10,18]. In our study, both male and female thyroid volumes were strongly correlated with BSA, and the quantile regression model coefficients for males and females reached 9.3 and 7.5, respectively, at the upper limit of the reference value.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Thyroid volume is closely related to anthropometric indexes, and the effect of BSA on thyroid volume has been widely confirmed [10,18]. In our study, both male and female thyroid volumes were strongly correlated with BSA, and the quantile regression model coefficients for males and females reached 9.3 and 7.5, respectively, at the upper limit of the reference value.…”
Section: Discussionsupporting
confidence: 72%
“…A study in areas with high iodine levels in China found that although age, sex, and BSA can affect thyroid volume in children, when stratified by age, this age-related difference only occurred in the 8-to-9year-old group. However, among adults, sex has always affected thyroid volume [17,18]. This may be due to the anatomically larger thyroid and higher lean body mass in males [17] as well as different hormone secretion levels in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation